単一細胞 RNA seq によるストレス応答性神経細胞の特性解析 - 中澤, 敬信; 笠井, 淳司; 奥野, 浩行; 山浦, 港生; 丹生, 光咲; 田沼, 将人; 勢力, 薫; 山口, 瞬; 橋本, 均 (日本薬理学会年会要旨集, 2019)
In order to address the mechanisms of stress response of the brain, it is important to characterize each stress responsive neuron. Recently, we performed whole brain imaging at single cell resolution in Arc-dVenus reporter mice, which express destabilized Venus in activated neurons. In these mice exposed to a stressor, dVenus signals were observed in a small brain region that strongly contributes to classifying stress and control brains. Here, we examined gene expression profiles of excitatory neurons in this region and compared stress responsive neurons with their neighboring non-responsive neurons using single-cell RNA sequencing. In Arc-dVenus mice, excitatory neurons were labeled by red fluorescent protein tdTomato using the AAV-PHP.eB vector. After the mice were subjected to a single social defeat stress, tdTomato-positive and dVenus-positive neurons were individually picked up and their gene expression profiles were compared. We identified the genes of which expression are induced by the stress and those that potentially classify the stress-responsive neurons from the non-responsive neurons. This study contributes to the understanding of the molecular basis of stress response and may open the door for specific analysis of stress responsive neurons.